Comparison of Au(III) Sorption on Amine-Modified Silica (AMS) and Quaternary Amine-Modified Silica (QAMS): A Thermodynamic and Kinetics Study - Ngatijo Ngatijo; Rahmat Basuki; Nuryono Nuryono; Bambang Rusdiarso (Indonesian Journal of Chemistry, 2019)
Amine-Modified Silica (AMS) and Quaternary Amine-Modified Silica (QAMS) has been synthesized through the sol-gel process for adsorption Au(III) in aqueous solution. The aim of this work was to compare the effect of addition three methyl group of AMS to form QAMS on its character, thermodynamics and kinetics parameter of sorption of Au(III) in aqueous solution. Characterizations performed by FT-IR, XRD, SEM and BET analyzer. Sorption study was carried out in a batch system under the various experimental conditions including the effect of medium acidity, a variation of Au(III) concentration (thermodynamics study), and variation of contact time (kinetics study). Optimum pH of sorption Au(III) on AMS was 3 and shift into 5 on QAMS. Thermodynamics sorption study by Langmuir isotherm models indicates that there was an increase of sorption capacity from 37.94 mg/g (AMS) to 74.47 mg/g (QAMS). Kinetics sorption studies by Lagergren, Ho, and RBS models indicate that the sorption Au(III) in this research fitted well with the RBS models. The addition of 3 methyl group also increased the sorption rate of Au(III) on QAMS (ka = 77.29 min-1 (mole/L)-1) over AMS (ka = 69.22 min-1 (mole/L)-1) and reinforce the electrostatic interaction between active site of QAMS.